KEBERAGAMAN KONTEN BERITA PANDEMI DI INDONESIA: ANALISIS ISI BERITA COVID-19 PADA MAJALAH TEMPO - Ahsani Taqwim Aminuddin (Master of Communication Science Program, Universitas Diponegoro, 2023)
This study shows how Tempo Magazine practices content diversity in reporting on the COVID-19 pandemic in Indonesia. The role of the media in handling the pandemic is not only limited to massive reporting but must report all aspects of life affected by the pandemic as information to the public. The concept of diversity in news content is the main study in this research. This concept examines two things: 1) Diversity of news sources, to determine the diversity of news sources (social actors). 2) Diversity of topics (points of view) to find out how widely the media provides understanding to media audiences regarding the issue of the COVID-19 pandemic. Using qualitative content analysis, and processing by coding with QDA Miner to summarize news frames regarding the COVID-19 pandemic news in Majalah Tempo from April to November 2021. The results of this research show that news about the COVID-19 pandemic in Indonesia in Tempo Magazine is presented from various sources. point of view or angle, news source, and spread across various rubrics. This study found that Majalah Tempo’s reporting on the COVID-19 pandemic was presented in various ways, both in terms of news sources, the point of view of discussing a problem, and the distribution of news presentation rubrics. Research notes that Inforial (paid rubric) is included in the rubric that contains a lot of COVID-19 news in Tempo Magazine with a percentage of 11.68%, apart from that the government is the largest news source with a percentage of 40.33%.